2018
DOI: 10.4028/www.scientific.net/df.16.45
|View full text |Cite
|
Sign up to set email alerts
|

Non-Newtonian Power-Law Flows around Circular Cylinder under Aiding/Opposing Thermal Buoyancy

Abstract: This paper presents a comprehensive computational work on hydrodynamic and thermal phenomena of upward flow separation around a confined circular cylinder by aiding/opposing thermal buoyancy. For that purpose, let us consider a confined flow of Non-Newtonian power-law fluid around a heated/cooled circular cylinder in a two-dimensional vertical channel. The effects of thermal buoyancy and power-Law index on the flow separation and the average Nusselt number are studied for the conditions: (10 ≤ Re ≤ 40), (0.4≤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…In order to verify the numerical methodology, sets of comprehensive numerical tests are conducted to evaluate the accuracy of our results in comparison with other available numerical investigation of D. chatterjee et al [14] and Aboueian J. et al [15]. The results of validation are available at [13]. As presented in this paper, a good agreement is observed between present work and the previous researches.…”
Section: Validation Testsupporting
confidence: 76%
See 2 more Smart Citations
“…In order to verify the numerical methodology, sets of comprehensive numerical tests are conducted to evaluate the accuracy of our results in comparison with other available numerical investigation of D. chatterjee et al [14] and Aboueian J. et al [15]. The results of validation are available at [13]. As presented in this paper, a good agreement is observed between present work and the previous researches.…”
Section: Validation Testsupporting
confidence: 76%
“…In order to understand the effects of thermal buoyancy on Newtonian and non Newtonian fluid flow and heat transfer, Laidoudi H. et al performed a series of researches [11][12][13]. In the first work [11], the effect of superimposed thermal buoyancy as well as asymmetrically confined circular cylinder submerged in incompressible Poseuille liquid, this work is done only at fixed value of blockage ratio B = 20%, the governing equations of continuity, momentum and energy have been solve by the ANSYS-CFX Software.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many research works are available in the literature that devoted for fluid flow and heat transfer around circular cylinder. The majority of these works emphasize on thermohydrodynamic characteristics of fluid subjected to aiding thermal buoyancy for flow around confined cylinder [4][5][6][7][8]. The principal parameter that controls a relative effect of buoyancy is the Richardson number Ri, defined as Ri = Gr / Re2, where, Gr is Grashof number, and Re is Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…The Strouhal, Nusselt numbers are also calculated in this work. Laidoudi H. et al [6] they studied numerically the effect of aiding thermal buoyancy on the distribution of local Nusselt number around a confined square cylinder, a vertical Non-Newtonian flows of power low fluids are used in this word for this range of conditions: Re = 20, Ri = 0 to 0.5, n = 0.4 to 1.2. The results showed that, when the thermal buoyancy is superimposed, the recirculation zone disappeared at all behind the cylinder, and the local Nusselt number decreased behind the object.…”
Section: Introductionmentioning
confidence: 99%